ENHANCED PERFORMANCE OF DYE SENSITIZED SOLAR CELL (DSSC) DIVACES BY UTILIZING PLASMON RESONANCE EFFECT FROM GOLD NANOPARTICLES - Zahrotul Aghniya, Shofy
Dye Sensitized Solar Cell (DSSC) is a type of third generation solar cell which has advantages including: simpler and easier fabrication methods; low production costs; using environmentally friendly materials; ability to work at wide angles, low light intensity and diffused light; exhibits little change in performance at ambient temperatures from -20oC sampai 80oC; and flexible. In recent years there have been many studies related to increasing the efficiency and life time of this type of solar cell, one of which is to take advantage of the effect of localized surface plasmon resonance (LSPR) into the DSSC structure either into the dye layer or forming a separate layer structure. LSPR is an optical phenomenon produced by light waves trapped in metal nanoparticles because their size is smaller than the wavelength of the light that hits them. When the oscillation frequency of the free electrons on the metal surface matches the frequency of the electromagnetic waves from the incident light, it will produce a very large electric field around the metal surface. In this study, the effect of adding gold nanoparticles (AuNP) to the dye layer was studied, which was expected to help absorb photons and improve device performance. In addition, the effect of variations in the use of organic capping materials on AuNP was also studied, both on changes in optical and chemical characteristics when added with N-719 dye solution. In this study the capping materials used were limited to oleylamine and 3-mercaptopropionic acid materials because they are known to have high stability when functionalized as a stabilizer and capping of Au core. Synthesis of gold nanoparticles with capping oleylamine (AuOA) and 3-MPA (AuMPA) was done using the chemical reduction method. Meanwhile, DSSC fabrication with addition of AuNP was carried out using a mechanism similar to that developed in previous studies. Material characterization and device measurement includes UV-Vis spectroscopy characterization, FTIR spectroscopy characterization, Raman spectroscopy characterization, SEM characterization, and J-V measurement. The results of the UV-Vis spectroscopy characterization showed that the specific plasmonic peak for AuOA and AuMPA solutions was at the same wavelength, at 530,97 nm. Meanwhile, the absorbance area of the N-719 dye solution has a broadening of the band due to the addition of AuOA solution, this occurred due to the possibility of disturbance in the chemical structure of the N-719 dye. The formation of a chemical bond between dye N-719 and the capping material oleylamine or 3-MPA is indicated by a shift in the band from the observations of the FTIR and Raman spectra. The SEM image results show that the mesoporous area of the TiO2 layer has been successfully prepared and for the TiO2 layer soaked in N-719 dye with the addition of AuNP, it shows the growth of AuNP (bright white in color) measuring about 52 nm, above the surface. The fabricated DSSC device then measured its electrical properties using a solar simulator with an intensity of 1000 W/m2 . The J-V measurement results show that the DSSC device with the addition of AuNP has a ???????????? of 17,09 mA/cm2 and ???????????? of 0,71 V compared to the reference device which has a ???????????? of 16,93 mA/cm2 and a ???????????? of 0,7 V, where in this initial study the device efficiency was obtained by adding AuNP increased by 0,16%.